CHARACTERIZATION OF A HIGH EFFICIENCY SILICON PHOTOMULTIPLIER FOR MILLISECOND TO SUB-MICROSECOND ASTROPHYSICAL TRANSIENT - Li, Siyang; Smoot, George F. (arxiv, 2020)
We characterized the S14160-3050HS Multi-Pixel Photon Counter (MPPC), a high efficiency, single channel silicon photomultiplier manufactured by Hamamatsu Photonics K.K. All measurements were performed at a room temperature of (23.0 ± 0.3) °C. We obtained an I-V curve and used relative derivatives to find a breakdown voltage of 38.88 V. At a 3 V over voltage, we find a dark count rate of 1.08 MHz, crosstalk probability of 21 %, photon detection efficiency of 55 % at 450 nm, and saturation at 1.0x1011 photons per second. The S14160- 3050HS MPPC is a candidate detector for the Ultra-Fast Astronomy (UFA) telescope which will characterize the optical (320 nm - 650 nm) sky in the millisecond to sub-microsecond timescales using two photon counting arrays operated in coincidence on the 0.7 meter Nazarbayev University Transient Telescope at the Assy-Turgen Astrophysical Observatory (NUTTelA-TAO) located near Almaty, Kazakhstan. We discuss advantages and disadvantages of using the S14160-3050HS MPPC for the UFA telescope and future ground-based telescopes in sub-second time domain astrophysics.
Keywords: Type of access: Open Access; silicon photomultiplier; instrumentation; telescope; detector characterization; high efficiency; astro-physical transients; quantum optics